Pengaruh Variabel Ekonomi Makro Terhadap Return Saham Properti Pada Bursa Efek Indonesia - Nurhidayat, R (Jurnal Kajian Ekonomi dan Keuangan, 2009)
The purpose of this paper is to provide an analysis of the long-run equilibrium relationships between the four macroeconomic variables and property stock index return of Jakarta Stock Exchange. In addition, a dummy variable is included to capture the impact of crisis. The macroeconomic variables analyzed are interest rate, inflation rate, exchange rate, and market return of Jakarta Stock Exchange using monthly observations from January 2003 through December 2008. Ordinary leased square is used to test these relationships. Signal approach is also employed to identify crisis happened during last five years in Indonesia. Econometric result finds long- run equilibrium and significant relationship between Property stock index return and the macroeconomic variables. Finally, there are two crisis periods during last five years in Indonesia. The crises have negative effect on the stock return